2018
DOI: 10.1097/wno.0000000000000580
|View full text |Cite
|
Sign up to set email alerts
|

Altered Macular Microvasculature in Mild Cognitive Impairment and Alzheimer Disease

Abstract: Patients with AD had less density of retinal microvascular networks than controls. Our findings suggest the presence of retinal microvascular dysfunction in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
207
6
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(233 citation statements)
references
References 34 publications
(55 reference statements)
10
207
6
3
Order By: Relevance
“…In those with mild cognitive impairment, only the density of the superior deep vascular plexus is decreased. This suggests a compromise, possibly at the level of the ganglion cell layers, which supports the argument that loss of ganglion cells, because of compromised vascular networks, may contribute to a thinner macula. OCT‐angiography is superior to fluorescein angiography in that it is non‐invasive, with no side effects, and provides detailed information about the superficial, deep and the middle capillary plexus …”
Section: Alzheimer's Diseasesupporting
confidence: 73%
“…In those with mild cognitive impairment, only the density of the superior deep vascular plexus is decreased. This suggests a compromise, possibly at the level of the ganglion cell layers, which supports the argument that loss of ganglion cells, because of compromised vascular networks, may contribute to a thinner macula. OCT‐angiography is superior to fluorescein angiography in that it is non‐invasive, with no side effects, and provides detailed information about the superficial, deep and the middle capillary plexus …”
Section: Alzheimer's Diseasesupporting
confidence: 73%
“…Three of these focused on CI, and even with differences in ROI, imaging device, vessel segmentation software, FD calculation method and software, all three confirmed a significant decrease of FD measures in CI (including dementia) (Cabrera DeBuc et al, 2018), mild CI (Jiang et al, 2018) and AD (Csincsik et al, 2018). After a follow-up period of 2 years, Csincsik et al reported that the significant difference in FD between AD and controls at baseline had become a trend (Csincsik et al, 2018), whereas Jiang et al described a trend of vascular density loss from controls over MCI to AD cases (Jiang et al, 2018). A significant association between fractal dimension and Montreal Cognitive Assessment (MoCA) could not be confirmed (Cabrera DeBuc et al, 2018).…”
Section: Outcomes Of Fractal Analysis In Studies On Neurodegenerativementioning
confidence: 89%
“…Jiang et al have reported differences using fractal analysis on OCTA superficial and deep capillary plexus between patients with AD and control subjects. 25…”
Section: Practical Retinamentioning
confidence: 99%